B2B sales strategies of freight forwarding industries- an in depth study of Kuehne + Nagel Bangladesh Limited - Anik, Ariful Mahbub (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.